RETRACTED: Bridging the mental health gap: unveiling and mitigating the hidden toll of workplace behaviors on diverse populations - Zou, Yang (Frontiers in Public Health, 2023)
This study investigates the critical issue of mental health disparities within diverse populations in modern workplaces, a concern that significantly affects both individuals and organizational structures. By focusing on how prevailing workplace behaviors, including implicit biases, microaggressions, and the scarcity of diversity in leadership, exacerbate these disparities, the research highlights the urgent need for attention and action in this area. The mental health gap—disparities in conditions and access to care among different workplace groups—emerges from systemic inequalities and stigmatization, deeply influencing employee productivity, creativity, collaboration, and retention. Our research underscores the disproportionate impact of this gap on diverse populations, characterized by varying ethnicity, gender, age, socio-economic status, and other unique identity attributes. The paper articulates the substantial economic repercussions for organizations, manifesting as reduced productivity, increased absenteeism, and higher turnover rates. Recommendations include the implementation of cultural competency training, promotion of inclusive leadership, investment in tailored mental health resources and fostering open dialog about mental health. These strategies are pivotal in creating an inclusive, resilient, and harmonious work environment. Our findings aim to catalyze a shift in organizational practices toward mental well-being, advocating for comprehensive strategies to bridge the mental health divide in workplaces, thereby enhancing overall organizational health and cohesion.